Diagnosing Moral Foundations: Testing of the Russian Version of the Moral Foundations Questionnaire - Oleg A. Sychev; Irina N. Protasova; Konstantin I. Belousov (Российский психологический журнал, 2018)
Introduction. The Moral Foundations Questionnaire (MFQ), developed on the basis of J. Haidt’s moral foundations theory, has become a popular tool for studying morality. The questionnaire contains five scales corresponding to moral foundations – namely, harm/care, fairness/reciprocity, in-group/loyalty, authority/respect, and purity/sanctity. Despite moderate reliability of the scales, the technique can be instrumental in identifying moral foundations of social stereotypes and political beliefs in Russian samples, as well as in developing Russian instruments for diagnosing individuals’ morality. This study presents the psychometric characteristics of the MFQ Russian version and provides new evidence of the relationship between moral foundations and other variables.